Dispersion of Li[Ni0.2Li0.2Mn0.6]O2 Powder by Surfactant for High-power Li-ion Cell - Su Hyun Yun; 박용준 (Bulletin of the Korean Chemical Society, 2009)
The particle size of Li[Ni0.2Li0.2Mn0.6]O2 cathode powder was controlled effectively by dispersion using lauric acid as a surfactant. The samples treated by lauric acid showed smaller particles of approximately half the original size compared to the particles of a pristine sample. A structural change due to the dispersion of Li[Ni0.2Li0.2Mn0.6]O2 powder was not detected. The rate performance of the Li[Ni0.2Li0.2Mn0.6]O2 cathode was improved by dispersion using lauric acid, which was likely due to the decrease of the particle size. In particular, a sample dispersed pristine powder using lauric acid (L2) presented a greatly enhanced discharge capacity and capacity retention at a high C rate. The discharge capacity of a pristine sample was only 133 mAhg-1 (3C rate) and 96 mAhg-1 (12C rate) at the tenthcycle. In contrast, the L2 electrode delivered higher discharge capacities of 160 mAhg-1 (3C rate) and 129 mAhg-1(12C rate) at the tenth cycle. The capacity retention at a rate of 12C/2C was also enhanced from ~ 45% (pristine sample) to 57% (L2) by treatment with lauric acid. KCI Citation Count: 1